2015
DOI: 10.18632/oncotarget.4256
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of the candidate tumor suppressor gene ASC/TMS1 in human renal cell carcinoma and its role as a potential therapeutic target

Abstract: This study investigated the epigenetic alteration and biological function of the pro-apoptotic gene ASC/TMS1 in renal cell carcinoma. ASC/TMS1 was downregulated in five out of six RCC cell lines. A significant downregulation was also detected in sixty-seven paired renal tumors compared with adjacent non-cancerous tissues. The downregulation of ASC/TMS1 was correlated with promoter hypermethylation and could be restored with demethylation treatment. Re-expression of ASC/TMS1 in silenced RCC cell lines inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
0
31
1
Order By: Relevance
“…ASC-expressing cells exhibited increased apoptosis at a high cell density. ASC has been reported to play an essential role in the intrinsic mitochondrial pathway of apoptosis through a p53-Bax network [27], with the anti-tumorigenic function of ASC being partially regulated by the activation of p53 and p21 signaling [17]. However, experiments with shRNA revealed that the ASC-dependent apoptosis induced at a high cell density in this study was independent of p53 and p21.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…ASC-expressing cells exhibited increased apoptosis at a high cell density. ASC has been reported to play an essential role in the intrinsic mitochondrial pathway of apoptosis through a p53-Bax network [27], with the anti-tumorigenic function of ASC being partially regulated by the activation of p53 and p21 signaling [17]. However, experiments with shRNA revealed that the ASC-dependent apoptosis induced at a high cell density in this study was independent of p53 and p21.…”
Section: Discussionmentioning
confidence: 53%
“…Colorectal cancer was enhanced upon genetic deletion of caspase-1 or ASC [14], while ASC-overexpressing lymphoma cells showed reduced metastasis [15]. The understanding of the mechanisms of ASC has progressed as well, with reports of tumorigenesis inhibition in primary melanoma via ASC expression by restricting NF-κB activity [16] and decreased P53- and p21-related cell apoptosis by knockdown of ASC [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, the ectopic expression of ASC in human fibrosarcoma HT-1080 cells in which ASC expression is silenced by epigenetic regulation also resulted in the attenuation of cellular motility in scratch assays (our unpublished data). Liu et al [16] reported that ectopically expressed ASC suppressed RCC cell migration and invasion in 786-0 and A498 cells. Moreover, we demonstrated a higher experimental metastatic ability of ASC-knockdown B16BL6 cells to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Since Liu et al [16] reported that ASC overexpression suppressed cell migration and invasion in RCC cell lines, we next examined the effects of ASC-knockdown on the cellular motility of B16BL6 cells in scratch assays. Interestingly, cellular motility, or wound healing, was significantly enhanced in ASC-knockdown cells within 14 h of scratching ( Fig.…”
Section: Asc Silencing Significantly Enhanced the Motility Of B16bl6 mentioning
confidence: 99%
See 1 more Smart Citation